Respuesta :

Answer:

y = - [tex]\frac{1}{4}[/tex] (x - 1)²(x + 2)(x + 6)

Step-by-step explanation:

The roots from the graph are

x = - 6 , then factor is (x + 6)

x = - 2 , then factor is (x + 2)

x = 1 ( multiplicity 2 ) , then factor is (x - 1)² then

y = a(x - 1)²(x + 2)(x + 6) ← a is a multiplier

To find a substitute any point on the graph into the equation

Using (0, - 3 ), then

- 3 = a(- 1)²(2)(6) = 12a ( divide both sides by 12 )

- [tex]\frac{1}{4}[/tex] = a

Then

y = - [tex]\frac{1}{4}[/tex] (x - 1)²(x + 2)(x + 6)